Correlação entre sensibilidade in vitro de isolados clínicos de Leishmania chagasi à miltefosina e resposta ao tratamento - Rocha, Renata Monti (2012)
The miltefosine has been used successfully for treatment of VL in India, with a cure rate of 94%. However, a clinical trial demonstrated that, in Brazil, about 50% of patients with VL failed after treatment. One hypothesis to explain the occurrence of therapeutic failure in patients treated in Brazil would be the occurrence of variable sensitivity to miltefosine among L. chagasi isolate. The variation in the sensitivity to miltefosine has been related to differences in the ability to internalize the drug as a direct result of a defect in the translocation machinery present in the cell membrane of Leishmania, comprising at least two proteins, LdMT and its β subunit, LdRos3. Therefore, the objectives of this study were to evaluate the correlation of in vitro sensitivity to miltefosine in L. chagasi isolates with the response to treatment, and correlate miltefosine susceptibility with the expression of proteins related to their translocation machinery. Using macrophage infection assays, our results showed that all strains obtained from patients cured after treatment were susceptible to miltefosine in vitro (IC50 2.6 - 7.94 mM), whereas 10 of 12 samples of patients who presented treatment failure were resistant (IC50> 15 mM). Those two isolates that were sensitive pre-treatment have become resistant, indicating the acquisition of resistance during the treatment. Therefore, these data suggest that the treatment failure observed in patients with VL in Brazil is related to parasite drug resistance. On the other hand, the analysis of gene expression of proteins responsible for miltefosine uptake showed no difference between sensitive and resistant isolates. Considering these results, we believe that monitoring the sensitivity of clinical isolates of Leishmania to miltefosine is highly relevant for predicting treatment failure. Moreover, since in vitro infection of macrophages used to evaluate the parasite sensitivity to the drug is laborious and time consuming, the search for drug resistance markers using simple and rapid methods is important to facilitate this monitoring.